A Systematic Reading of “Philosophy through Science Fiction Stories: Exploring the Boundaries of the Possible “through the proposals of the editors: Helen De Cruz, Johan de Smedt, and Eric Schwitzgebel - AlSufyani, Amal A. (Dirasat: Human and Social Sciences, 2024)
Objectives: This article systematically examines the book "Philosophy Through Science Fiction Stories: Exploring the Limits of Possibility." It explores whether philosophy can be learned through science fiction stories, and effectively treats them as philosophical works. The aims are to review the significance of science fiction literature in presenting scientific boundary cases that prompt critical inquiry, to extract key philosophical questions from science fiction stories, to assess the influence of scientific progress on the book’s viewpoint, and to provide recommendations for enhancing science fiction literature. Methods: This study utilizes a four-level analytical approach: observation, reading and analysis, discussion, and synthesis. The observation level involves examining external book indicators like the cover, title, editors, and quotations to identify conveyed ideas or themes. Reading and analysis focus on the text, using the researcher’s notes and additional references to illuminate arguments. Discussion engages with the book’s proposals and its argumentative style, addressing the responses of the editors. The conclusion provides an overview of the findings. Results: The book uses science fiction as a narrative tool to explore three vital human aspects: the self, society, and theology, each represented in distinct sections. The first section explores the idea of improving the human lineage through science, the second explores relationships within society and individual values within different social contexts, and the third explores the intersection of religious philosophy and family dynamics. The study found that the book was able to discuss deep philosophical ideas smoothly using narrative style and well-crafted rhetorical strategies, which supports the effectiveness of using stories as a method to teach and learn philosophy. Conclusions: The review outlines three key theses presented by the editors regarding the central question. It also highlights the editors’ argumentative and conceptual approach in exploring science fiction as a form of philosophy, serving as the central axis encompassing all other aspects explored in the book.